Thermally activated twin thickening and solute softening in magnesium alloys - a molecular simulation study. (15th March 2019) - Yi, Peng; Falk, Michael L.
Abstract: Thickening of the tension twin 10 − 12⟨10 − 11⟩ in Mg-Al and Mg-Y alloys varies systematically with temperature, strain rate and solute concentration. The twin boundary propagates through the nucleation and expansion of twin dislocation loops, a thermally activated process. Solute softening is observed in both alloys. The softening saturates with increasing solute concentration due to solute hardening of twin dislocation loop expansion. With the present interatomic potential, Al solutes are more effective in both softening and hardening than Y solutes. Twin thickening exhibits weak strain rate sensitivity for pure Mg but the strain rate sensitivity increases with solute concentration. Graphical abstract: Unlabelled Image